Atomic-resolution analytical scanning transmission electron microscopy of topological insulators with a layered tetradymite structure - Danielle Reifsnyder Hickey (APL Materials, 2020)
The recent discovery of topological insulators has uncovered exciting new quantum materials with potential applications in the emergent fields of topological spintronics and topological quantum computation. At the heart of uncovering the new physical properties of these materials is the characterization of their atomic structures, composition, defects, and interfaces. The technique of atomic-resolution analytical scanning transmission electron microscopy has already provided many insights and holds great promise for future discoveries. This perspective discusses advances that have been achieved in the atomic-scale characterization of topological insulators with a layered tetradymite structure, and it proposes future directions to link atomic-scale features to exciting new physical phenomena.